Pengembangan LASMATH (Labirin SPLDV Matematika) untuk Memperkuat Numerasi Peserta Didik pada Materi SPLDV - Puspitasari, Ririn; Manoy, Janet Trineke (Universitas Negeri Surabaya, 2025)
This research aims to develop LASMATH learning media material to strengthen students’ numeracy and find out the result of learning media development in terms of validity, practical and effective. ADDIE development was used in this research model which consists of 5 stages, namely needs analysis, curriculum analysis, student analysis and media analysis. The Design stage involves looking for ideas application names, compiling flowcharts, compiling storyboards, background designs, and compilling questions. The Development stage carried out the development of LASMATH learning media, validation of media experts and material experts, media revision. The Implementation stage was implemented for class VIII students at SMP Negeri 1 Mantup. In the Evaluation stage, activities are carried out to analyze the results of the research that has been carried out. Based on the results of validation that has been carried out. LASMATH carried out media validation by media experts with a score of 77% with valid criteria. Material expert validation received a score of 80% with valid criteria. Learning media trials were carried out on 28 class VIII students at SMP Negeri 1 Mantup. After testing the results of the research carried out by evaluation, the learning media was called pratical from the results of the percentage of students responses which obtained a score of 82,7% with practical criteria. The learning media is said to be effective and there significant difference in the data results of students score before and after using the LASMATH learning media evidenced by N-Gain 0,70. The LASMATH learning media is effective medium category.